A Novel Strategy to Enhance Microfracture Treatment With Stromal Cell-Derived Factor-1 in a Rat Model - Mustapich, Taylor; Schwartz, John; Palacios, Pablo; Liang, Haixiang; Sgaglione, Nicholas; Grande, Daniel A. (Frontiers in Cell and Developmental Biology, 2021)
Background: Microfracture is one of the most widely used techniques for articular cartilage repair. However, microfracture often results in filling of the chondral defect with fibrocartilage, which exhibits poor durability. Stromal cell derived factor-1 (SDF-1) is a potent chemoattractant for mesenchymal stem cells (MSCs) and is expressed at high levels in bone marrow during endochondral bone formation. Integrating SDF-1 into an implantable scaffold may facilitate robust hyaline cartilage formation following microfracture via chemotaxis of MSCs and promotion of chondrogenic differentiation. Methods: Bone marrow-derived MSCs were harvested from the femurs of Sprague-Dawley rats. MSCs were characterized by flow cytometry and cell migration assays were performed to determine optimal SDF-1 concentration. A 1.6mm diameter hole was drilled into the femoral trochleae of 20 Sprague-Dawley rats bilaterally until bone marrow spillage was seen. One knee was randomly chosen to receive implantation of the scaffold, with the contralateral knee left unfilled. Collagen scaffolds were dip-coated with either gelatin only (N=10) or gelatin+SDF-1 (N=10). Femurs were collected for histological analyses at four and eight-week time points and sections were stained with Safranin O/Fast Green. Samples were graded blindly using the Modified O’Driscoll score. Quantitative comparisons were performed with one-way ANOVA analyses. Results: MSC migration showed a dose-response relationship with SDF-1, with an optimal dosage for chemotaxis between 10-100ng/ml. The SDF-1 group demonstrated complete filling of the cartilage defect with mature cartilage tissue exhibiting strong proteoglycan content and good incorporation into marginal cartilage. Modified O’Driscoll scores after eight weeks showed a significant improvement of repair in the SDF-1 group relative to the empty control (P = .009) and gelatin scaffold groups (P = .09). No significant differences were found between the empty defect and gelatin scaffold groups. Conclusion: We confirmed the chemotactic properties of SDF-1 on MSCs and found an optimized dosage range for chemotaxis between 10-100ng/ml. Further, we demonstrated a strategy to incorporate SDF-1 into implantable scaffolds to improve the quality of cartilage repair following microfracture. These results suggest that the recruitment of MSCs to the microfracture site via SDF-1 mediated signaling can significantly improve the quality of cartilage regeneration.